A review of developments in the methodology and application of microemulsion electrokinetic chromatography. Issue 1 (3rd December 2012) - Ryan, Richie; Altria, Kevin; McEvoy, Eamon; Donegan, Sheila; Power, Joe; Rassi, Ziad El
<x xml:space="preserve">Abstract</x> MEEKC is a mode of CE, which utilizes microemulsion (ME) as the BGE to achieve separation of a diverse range of analytes. MEs are composed of nanometer‐sized oil droplets suspended in aqueous buffer which are stabilized by the presence of a surfactant and co‐surfactant. These MEs are commonly referred to as oil‐in‐water MEs and their application in MEEKC has been extensively examined. This review details advances in the theory, methodology, and application of MEEKC during the period 2010–2012. Areas covered include online sample concentration, advances in chiral separations, use of coated capillaries, chemometric approaches, and the use of novel additives to the ME system. This review also provides the reader with an introduction to MEEKC and a presentation of recent applications.